THE INFLUENCE OF NOVELTY IN TOURIST ATTRACTIONS ON REVISIT INTENTIONS TO MALIOBORO, YOGYAKARTA - Nadia Candra Pramesti; Hartanti Woro Susianti; I Wayan Sukma Winarya Prabawa (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This research aims to determine the effect of Novelty on tourists' revisit intention in Malioboro, Yogyakarta. Novelty, in the context of tourism, refers to the unique and different experiences offered by a destination that can attract tourists to revisit. Revisit intention is the desire of tourists to return to a destination in the future. The study employs a quantitative approach with simple linear regression analysis using SPSS 24 software. The research involves 140 domestic tourist respondents who visited Malioboro. The results show that Novelty has a positive and significant effect on tourists' revisit intention. The analysis indicates a correlation coefficient between Novelty and revisit intention of 0.747, demonstrating a strong positive correlation between the two variables. The determination coefficient test resulted in an R square of 0.558, meaning that 55.8% of the variation in revisit intention can be explained by Novelty , while 44.2% is influenced by other factors outside this study. The partial t-test showed a t-count of 13.191, greater than the t-table of 1.977, with a significance value of 0.000 < 0.05, indicating that Novelty significantly affects tourists' revisit intention in Malioboro